Computed tomography findings of retinoblastoma patients at Cipto Mangunkusumo Hospital Jakarta (Faculty of Medicine Universitas Indonesia, 2009)
Aim As data of CT findings for retinoblatoma in Indonesia is not yet available, this study aimed to determine patient distribution and to describe CT findings of RB patients at Cipto Mangunkusumo Hospital. Methods From April 2004 to August 2007, CT scans were performed on 64 new patients of RB with clinical findings: leukocoria (19 patients), leukocoria with proptosis (41 patients), buphthalmus (2 patients) and red eyes (2 patients). The CT can was performed using single slice CT scan and multislice CT scan with axial and coronal section. The cases were categorized into 3 groups: grade I: tumor confined to the globe, grade II: tumor extended to orbital soft tissue or involved the optic nerve, and grade III: tumor extended beyond the orbit or intracranial space. The CT features were evaluated in each group for the presence of calcification, contrast enhancement and lateralization. Results Sixty four patients (30 females and 34 males) were evaluated. Age range: 3 months up to 9 years old; bilateral 20 patients, unilateral 44 patients. Six patients of 19 patients with clinical finding leukocoria were included in group I, and the remaining were included in group II. Twenty seven patients of 41 patients with proptotic eyes were included in group II, and the remaining were included in group III. Patients with clinical finding buphthalmus and red eyes were included in group II. All of the group I tumors (6 patients) showed calcification and enhancement. In group II (44 patients), calcification was detected in 41 patients, and there was no evidence of contrast enhancement in 6 patients. Group III (14 patients): no calcification in 2 patients, all of the tumors showed enhancement. Conclusion Our study showed calcification in 92% of RB. Calcification was not a favorable prognostic sign, because calcification was detected in almost all of the extraocular and intracranial tumors. Tumor enhancement was not correlated with extraocular tumor extension. The finding of leukocoria without proptosis could not exclude the presence of extraocular tumor extension. Suspicious intracranial invasion should be considered in proptotic RB patient. Most retinoblastoma cases in Indonesia are diagnosed at advanced stage, so that the objective of the therapy is life saving rather than visual salvation. (Med J Indones 2009; 18: 239-43)